2012
DOI: 10.1161/circulationaha.111.040360
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus as Primary Immunosuppression Attenuates Allograft Vasculopathy With Improved Late Survival and Decreased Cardiac Events After Cardiac Transplantation

Abstract: Background-We retrospectively analyzed the potential of sirolimus as a primary immunosuppressant in the long-term attenuation of cardiac allograft vasculopathy progression and the effects on cardiac-related morbidity and mortality. Methods and Results-Forty-five cardiac transplant recipients were converted to sirolimus 1.2 years (0.2, 4.0) after transplantation with complete calcineurin inhibitor withdrawal. Fifty-eight control subjects 2.0 years (0.2, 6.5 years) from transplantation were maintained on calcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 41 publications
(60 reference statements)
2
76
2
1
Order By: Relevance
“…can attenuate the progression of CAV after HTx (17,18). However, there have only been two previous trials investigating the effect of everolimus on CAV progression among de novo HTx recipients (6,7), and both studies investigated the effect of such therapy in combination with either full-dose or reduced CNI exposure.…”
mentioning
confidence: 99%
“…can attenuate the progression of CAV after HTx (17,18). However, there have only been two previous trials investigating the effect of everolimus on CAV progression among de novo HTx recipients (6,7), and both studies investigated the effect of such therapy in combination with either full-dose or reduced CNI exposure.…”
mentioning
confidence: 99%
“…CAV is a major cause of long-term mortality following heart transplantation [1][2][3][4][5][6][7][8][9][10] . CAV may affect up to 50% of patients 5 years after transplantation [11] .…”
Section: The Pathogenesis Of Cav: An Inflammatory Perspectivementioning
confidence: 99%
“…The use of sirolimus (SIR) has been proposed as a substitute for CNIs in cardiac transplant patient based on its role in renal function preservation and prevention of chronic allograft vasculopathy [76][77][78] . In fact, SIR, can prevent vascular remodeling and neointimal proliferation, two key components of CAV, by inhibiting smooth muscle cell (SMC) and fibroblast proliferation [7,28,[79][80][81][82][83][84][85][86] . SIR has been shown to reduce the incidence of acute rejection among renal-transplant recipients and to prevent CAV in animals [87] .…”
Section: Mtor and Mtor Inhibitorsmentioning
confidence: 99%
“…However, the retrospective nature of the design and the differences in criteria for the therapy changes, make the results less generalizable [153] . Moreover, a recent study reported that late conversion to PSIs is associated with necrotic plaque core and calcification of the plaque [154] .…”
Section: Proliferation Signal Inhibitorsmentioning
confidence: 99%